Chlorine leak on Mumbai port trust's Sewri yard: A case study - Rakesh Kumar Sharma; Raman Chawla; Surendra Kumar (Wolters Kluwer Medknow Publications, 2010)
Chemical emergencies involving hazardous chemicals are not uncommon in India. More than 25 incidents have been identified in National Disaster Management Guidelines - Chemical (Industrial) Disaster Management, released in May 2007. In a recent occurrence on the morning of 14 July 2010, nearly at 3:00 a.m., chlorine leak was reported from a gas cylinder referred as turner, weighing about 650 kg, corroding with time at the Haji Bunder hazardous cargo warehouse in Mumbai Port Trust, Sewri, affecting over 120 people in the neighborhood, including students, laborers, port workers and fire fighters, of whom 70 were reported critical. It has been observed to be a blatant case of ignorance and negligence as well as contraventions to the safety and environmental safeguard requirements under existing statues as well as non-maintenance of failsafe conditions at the site requisite for chlorine storage. The analysis revealed significant gaps in the availability of neutralization mechanism and the chlorine stored in open increased the possibility of formation of ingress mixture due to busting of chlorine filled tankers. The Government of India has institutionalized emergency preparedness framework at national, state and district level as envisaged in Disaster Management Act, 2005, to prepare the nation to mitigate such incidences, if all the preventive safety provisions fail. Ministry of Environment and Forests (MoEF) is preparing National Action Plan-Chemical (Industrial) Disaster Management based on National Guidelines to implement all the mechanisms of capacity development across the country.